To determine which radical expression is equivalent to \( \sqrt{2x^{15}y} \), let's simplify each of the provided options and see if any match \( \sqrt{2x^{15}y} \).
-
Option 1: \( \sqrt{56xy^2} \) \[ \sqrt{56xy^2} = \sqrt{56} \sqrt{x} \sqrt{y^2} = \sqrt{56} \cdot \sqrt{y^2} \cdot \sqrt{x} = \sqrt{56} \cdot y \cdot \sqrt{x} \] (No match, since 56 does not reduce to 2 and the \(x\) and \(y\) powers differ.)
-
Option 2: \( 5 \sqrt{6xy^2} \) \[ 5 \sqrt{6xy^2} = 5 \cdot \sqrt{6} \cdot \sqrt{x} \cdot \sqrt{y^2} = 5 \cdot \sqrt{6} \cdot \sqrt{x} \cdot y \] (No match.)
-
Option 3: \( 3 \sqrt{50x^2y} \) \[ 3 \sqrt{50x^2y} = 3 \cdot \sqrt{50} \cdot \sqrt{x^2} \cdot \sqrt{y} = 3 \cdot \sqrt{50} \cdot x \cdot \sqrt{y} \] (No match since \( \sqrt{50} \) is not the same as \( \sqrt{2} \).)
-
Option 4: \( \sqrt{60x^2y} \) \[ \sqrt{60x^2y} = \sqrt{60} \cdot \sqrt{x^2} \cdot \sqrt{y} = \sqrt{60} \cdot x \cdot \sqrt{y} = x \cdot \sqrt{60y} \] (No match.)
-
Option 5: \( \sqrt{30x^2y} \) \[ \sqrt{30x^2y} = \sqrt{30} \cdot \sqrt{x^2} \cdot \sqrt{y} = \sqrt{30} \cdot x \cdot \sqrt{y} \] (No match.)
After checking all the options, none of them simplify directly to \( \sqrt{2x^{15}y} \).
To simplify \( \sqrt{2x^{15}y} \) directly: \[ \sqrt{2x^{15}y} = \sqrt{2} \cdot \sqrt{x^{15}} \cdot \sqrt{y} = \sqrt{2} \cdot x^{7} \cdot x^{\frac{1}{2}} \cdot y^{\frac{1}{2}} = x^7 \sqrt{2xy} \]
Thus, none of the given radical expressions simplify to \( \sqrt{2x^{15}y} \).